PERAN LSM FITRA DALAM PENGAWASAN PELAKSANAAN APBD JAWA TENGAH (studi kasus APBD Bantuan Sosial Provinsi Tahun 2012) - Lalu, Rilistyan; Widayati, Wiwik; Utomo, Susilo (Journal of Politic and Government Studies, 2013)
ABSTRACTThis research was conducted to examine the extent of the role of NGOs in the monitoring of the Fitra Budget Central Java in particular social assistance in 2012 and the circumstances of the results of monitoring conducted by FITRA . The purpose of this study is to find out what FITRA as a form of their role in monitoring the budget in Central Java , an approach like what they are doing to oversee ABBD and how the results of the monitoring they do . This study used a qualitative approach using the techniques of interview and documentation . Source of data derived from primary data collected by the data itself comes from an interview researchers who presented to the NGO board FITRA Central Java , Team Budget of the Region. while secondary data is data that is supportive discussion or data obtained from books , magazines and journals . Techniques of data analysis done with interviews and documentation . The survey results revealed that the actual role of FITRA have no proof but not so the maximum is since FITRA standing in Central Java, they do a lot of activities such as collect data relating to the budget then their input and their analysis . Having analyzed FITRA also conduct a public hearing and to disseminate to the public and then make recommendations to the government . However, the monitoring is done by FITRA not seen such a large role . Means especially for social grants in 2012 have not been up evidence FITRA role in channeling aid to the new role do the picking of the CPC test , so according to the researcher 's role will be better when FITRA straight down to the ground . Sehingganya for himself in 2012 when it discovered a new finding about the diversity of misappropriation of social aid funds then this could be one contributing factor is not the role of the NGOs FITRA in overseeing the distribution of social grants . apart because of all the government agencies have not been open to the public . Therefore , FITRA a need to increase the role of the more leverage in controlling the budget especially social assistance . the government should also be more open to the public on information that it should be accessible to the public .